The Election of the Big 4 Audit Firms In Mexico An Empirical Analysis (2000-2007) - Toscano Moctezuma, Juan Alfonso; Benau, María Antonia García (Archives of Business Research, 2015)
In this article, we present the results of an empirical study on the factors that determine the election of the Big 4 in Mexico during the period from 2000 to 2007. To this purpose, we have estimated a logistic regression model using a sample of companies listed on the Mexico Stock Exchange and its financial statements audited by an independent auditor. The results indicate that corporate features such as; the presence of controlling shareholders, the debt level, the presence of foreign investors, business size and requirement for additional services by audited companies are some of the factors determining the election of the Big 4 in Mexico.